Effect of different cooking conditions on the profiles of Maillard reaction products and nutrient composition of hairtail (Thichiurus lepturus) fillets. (January 2018) - Semedo Tavares, Wilson P.; Dong, Shiyuan; Jin, Weiya; Yang, Yuhong; Han, Kaining; Zha, Fengchao; Zhao, Yuanhui; Zeng, Mingyong
Abstract: Much attention has been given to investigate the formation of Maillard reaction products in thermal processing food due to potential health risks. This study aimed to the profiles of Maillard reaction products (MRPs) and changes of nutrient composition in hairtail ( Thichiurus lepturus ) fillets prepared by three cooking method: boiling, baking and frying. The N ε -carboxymethyllysine (CML) level ranged from non-detectable to 4.24 mg/100 g protein and furosine ranged from 4.25 to 20.95 mg/100 g protein. The levels of CML and furosine in boiled hairtail fillets were much lower than baked and fried ones. The formation of CML was only affected by the cooking method. The changes of the lipid and moisture content, and thiobarbituric acid-reactive substances (TBARS) content in cooked hairtail fillet had different effects on the formation of different stages of Maillard reaction. Furosine level significantly correlated with absorbance in 420 nm (r = 0.74, p < 0.05) and 280 nm (r = 0.73, p < 0.05) and fluorescence Intensity (FI) (r = 0.65, p < 0.05), but did not correlate with CML. The CML level linearly correlated with the moisture (r = 0.79, p < 0.01) and lipid content (r = 0.73, p < 0.05), and the formation of TBARS value (r = 0.92, p < 0.01), but did not correlate with the FI. Overall, the findings may help to better control the cooking conditions of hairtail meat based on the profiles of MRPs. Graphical abstract: Highlights: The profiles of MRPs in cooked hairtail fillet were investigated. The CML level was less affected than other MRPs by the extent of cooking. The TBARS value in cooked fillet significantly correlate with the CML level.